Determinación De La Situación Actual Del Virus De La Rabia En Quiropteros De Diferentes Localidades Del Departamento Del Quindío (2012)
The aim of this study was to determine the presence or absence of rabies virus in bats from different localities of the department of Quindío. The research was carried out in 15 months’ time which made 12 sacks in 9 locations in 7 municipalities in the department of Quindío. We captured a total of 44 individuals, belonging of two families, ten genera and twelve species of bats captured linear measurements were taken and were photographed and identified in situ. 12 individuals were collected for the study of rabies. The sampling for the diagnosis was made in the microbiology laboratory of veterinary diagnostic center Colombian Agricultural Institute (ICA) Quindío sectional based on the manual of procedures for the control and eradication of animal health risks of ICA. The samples were sent to the national laboratory in Bogotá, where diagnosis was made using wild rabies antibody titration techniques, direct inmunofluorescence and mouse bioassay. None of the bats submitted for diagnosis is evident through the presence of rabies virus. The most abundant species in the sample was Desmodus rotundus, with 19 individuals corresponding to 43.18% of relative abundance. The total capture effort in the sampling period was from 1,287 hours / network with a total capture success of 0553 Ind / time / network. Most of the bats captured were found in shelters and wells in which we obtained 15 individuals of three different species of bats Paper no vampire in the spread of rabies has been widely established in the United States, Canada, Europe, Asia and some parts of Latin America.